Capital Budgeting Analysis Case Study Surfcamp Resort Development at Kepulauan Mentawai by PT XYZ - Robert J.S Najoan; Hanandewa Hanandewa (Interdisciplinary Social Studies, 2026)
The purpose of this study is to find out how feasible the investment to be made in the investment project to be made in the surfcamp resort construction investment project at the old Rohot airport, Mentawai Islands using analysis in capital budgeting. This study is a type of descriptive quantitative analysis research where the research is to see the feasibility of investment in the construction of surfcamp resorts using capital budgeting analysis using Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period and Profitability Index. The data collection technique in this study is through a survey to the location of the investment plan, conducting data collection through structured interviews with the management of PT XYZ and the Mentawai Regency Government. Taking into account a weighted average capital cost of 9.28%, the management of the surfcamp at the old Rohot Airport will produce a Net Present Value (NPV) of IDR 48.3 billion, an Internal Rate of Return (IRR) of 30.64%, and a Profitability Index (PI) of 3.64x, where all indicators show that the surfcamp project is feasible to be implemented. Meanwhile, the results of the Payback Period analysis from Surfcamp are 5 years and 6 months, which is still within a reasonable range for property development projects.